Farmers’ Perception on the Establishment of Knowledge Centres in Coastal and Tribal Areas of Gujarat - P. Mahalakshmi, C. Gopal, M. Muralidhar, Prem Kumar, P.K. Patil, M. Kailasam, H.G. Solanki, R.V. Borichangar and J.G. Vanza, (Indian Journal of Extension Education, 2018)
This study was undertaken in Gujarat to analyse the farmers’ perception on the establishment of knowledgecentres in coastal and tribal areas. Among the various services, all the respondents needed details on theaquaculture practices, market pricing, and e-mail/internet facilities in the centre for upgrading their knowledgein aquaculture and better communication among the fellow farmers and experts respectively. Farmers stronglyagreed that the knowledge centre is necessary for coastal and tribal development. It is also essential forgetting information quickly and useful for decision making in cultural practices. The respondents ranked unityamong the village people as the major challenge for implementation of the centre with a rank-based quotientof 89.58 followed by the requirement of sustainability in both content and finance (85%) and interest in usageof advance technologies like computer, internet etc. among the farmers (83.33%). Adequate training shouldbe given to the farmers are also suggested for better utilization of ICT tools. The training in advanced technologyhelps the farmers to increase their efficiency and profitability of aquaculture production. Overall opinion forthe establishment of centre and the improvement of the initiatives are also discussed.